A study on the communication dynamics of the Tapatan Press Conference of the (BPI) Bureau of Public Information in the (ORG-ARMM) office of the regional Governor in Autonomous Region in Muslim Mindanao - Pelaez Marc Rayjen E.
The study investigate on the Tapatansa ARMM press conference meeting as a small group that processes information about whereabouts of the ORG-ARMM Region. The study looks into the Tapatansa ARMM press conference meetings as systems that adapt and maintain group practices and rules that are made possible through the key roles being portrayed by its participants (task-orientedness , social and self-maintenance) and the process elements (leadership, influence, cooperation, competition, participation, and communication) that influence the group discussion. The study considers on the interaction processes prevalent in the Tapatansa ARMM discussion group which are supposed to affect the efficacy of the group communication and performance. The study makes an effort to explore on the people and group processes particularly in the press conferences and investigates on the unique and ever-growing group dynamics in the Philippine context and the Philippine culture
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication